Beyond the end of the world - Kaufman, Amie; Spooner, Meagan (HarperTeen, an imprint of HarperCollinsPublishers, 2022)
"Above, in the cloudlands, Nimh has no memory of her past, only an aching, undying certainty that she has left something -- someone -- behind. Below, on the surface, North looks to the sky, desperate to join the person he loves and return to his world. In their desperation to reunite and save their people, Nimh and North face one ultimate question: can they defy their love and their destiny to save their homes? Or will the spark between them ignite their worlds, and consume them all together?"-- Provided by publisher
Sequel to: The other side of the sky
Keywords: Love / Young adult fiction; Prophecies / Young adult fiction; Princes / Fiction; Magic / Fiction; Fate and fatalism / Fiction; Young adult fiction; Princes / Romans, nouvelles, etc; Destin et fatalisme / Romans, nouvelles, etc; Roman pour jeunes adultes; Fantasy; Fantasy fiction; Young adult works; Novels; Romans; Jugendbuch